DESAIN MANAJEMEN LAYANAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK ITIL DOMAIN SERVICE TRANSITION DAN SERVICE OPERATION - Rahayu, Aulia Putri Restu; Kurniawan, Yudhi (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2023)
Universitas Ma Chung is one of the developing universities that continually maintains the quality of its education, as evidenced by the excellent support provided by its SI/IT programs. Universitas Ma Chung has an administration that manages technology or information systems, which has been continuously developing to this day. The technology or information system administration encompasses various aspects, such as IS/IT strategic planning, IS/IT risk management, IS/IT service management, IS/IT security management, procurement and investment of IS/IT assets, and IS/IT audits. This study focuses on IS/IT service management at Universitas Ma Chung. Based on the 2020-2024 IS/IT development strategy planning document, IS/IT administration has not been optimally implemented concerning the availability of standard operating procedures (SOPs) for IS/IT, especially IS/IT services at Universitas Ma Chung. This study utilizes the third version of the ITIL (Information Technology Infrastructure Library) framework with the service transitions and operations domains. In this study, a mapping of policies and a list of standard operating procedures were carried out. Based on the mapping results, standard operating procedures for IT services at Universitas Ma Chung were developed, allowing these procedures to be implemented in daily operations at the university.